'It’s almost like talking to a person': Student disclosure to pedagogical agents in sensitive settings - Tombs, Gemma; Bhakta, Roy; Savin-Baden, Maggi (Proceedings of the International Conference on Networked Learning, 2014)
It would seem that emerging communication technologies are disrupting and changing societal norms and conventions. The literature suggests central to making sense of the unique qualities of cyberspace are understandings of such social networks, veracity and the differences between online and offline behaviour. We propose that as pedagogical agents are seen to help support and even improve the level of interactive learning on a programme or course, it is essential that these societal norms and behaviours are considered within pedagogical agent learning situations. Pedagogical agents are characters on the computer screen with embodied life-like behaviours such as speech, emotions, locomotion, gestures, and movements of the head, the eye, or other parts of the body. This paper presents findings of a pilot study that used pedagogical agents to examine disclosure in educational settings. The study used responsive evaluation to explore how the use of pedagogical agents might affect students’ truthfulness and disclosure by asking them to respond to a lifestyle choices survey delivered by a web-based pedagogical agent. The findings of this study suggest that 3 key issues are important; firstly the pedagogical appearance of the agent, secondly, the issue of choice and finally that of disclosure. Data also suggested that body language is critical to the learning effectiveness of pedagogical agents. The appearance of the pedagogical agent and the images it invoked, determined partially by students’ ability to choose their own pedagogical agent, were found to play a role in students’ willingness to disclose information. Qualitative findings from users also suggested that they may feel comfortable disclosing more sensitive information to pedagogical agents than to the interviewer. Our findings support the growing body of literature which suggests that the social environment of cyberspace is characterised by more open, straightforward and candid interpersonal communication, and that a pedagogical agent can support this. Findings indicate that emotional connection with pedagogical agents were intrinsic to the user’s sense of trust and therefore likely to affect levels of truthfulness and engagement. The implications of this study are that truthfulness, personalisation and emotional engagement are all vital components in using pedagogical agents to enhance online learning.